Pengaruh Tenaga Kerja, UMP Dan PAD Terhadap PDRB Per Kapita Di Wilayah Sumatera 2010-2020 - Saskia, Nadia Shafa; Yusnida (Convergence: The Journal of Economic Development, 2022)
This study aims to analyze the effect of labor, UMP and PAD on GRDP per capita. The components used in this study include labor, UMP and PAD. The method in this research is explanatory research and uses panel data regression analysis with cross section data for 10 provinces and time series data for 11 years. The results of this study indicate that Manpower, UMP and PAD simultaneously affect GRDP per capita in Sumatera 2010-2020. Labor variable has a positive and significant effect on GRDP per capita with a coefficient value of 4.531552 and a significance value of 0.0067 which is smaller than 0.05. The UMP has a positive and significant effect on GRDP per capita with a coefficient value of 0.859076 and a significance value of 0.0019 which is smaller than 0.05. PAD has a positive and significant effect on GRDP per capita with a coefficient value of 0.000148 and a significance value of 0.0067 which is smaller than 0.05. The value of Adj.R2 is 0.9836, this shows that 98.36% of the change in GRDP per capita can be explained by changes in the three independent variables consisting of Manpower, UMP and PAD. While the remaining 1.64% can be explained by other variables not included in this study. Keywords : Labor1, UMP2, PAD3, GRDP per capita4